Production of foot-and-mouth disease virus SAT2 VP1 protein - Mpho Victoria Mamabolo; Jacques Theron; Francois Maree; Michael Crampton (AMB Express, 2020)
Abstract The seven serotypes of foot-and-mouth disease virus (FMDV) differ on the surface exposed regions on the VP1, 2 and 3 proteins. Amongst the three, the VP1 protein has been produced the most for use in serotyping assays for some of the Euro-Asian serotypes. In this study the VP1 protein of the FMDV SAT2/ZIM/7/83 was expressed in Escherichia coli BL21 cells in Luria broth and EnPresso® B media in shake flasks. Production was further developed and the VP1 protein was produced at 2.15 g L−1 in fed-batch fermentations at 2 L scale. The protein formed insoluble inclusion bodies that were isolated, denatured and refolded. When tested in ELISA, the protein was found to be highly reactive with serum from a SAT2 vaccinated guinea pig, and not reactive to SAT1 and SAT3 antisera. These results open avenues to evaluate recombinantly expressed VP1 proteins for differentiation of the three Southern African Territories serotypes of FMDV that co-occur in Southern and East Africa. In addition, this could mitigate the need for employing virus as reagent, or having to raise reagent antibodies.